The importance of brand equity to University College Sabah Foundation (UCSF) / Mohd Syuwari Abduh - Abduh, Mohd Syuwari (2018)
The purpose of this research is to study on the importance of brand equity to University College Sabah Foundation (UCSF). Branding is considered as the most crucial element to develop sustainable strategies agreed among universities and colleges. However, because of the uncommon nature of the service, the result is more likely to become adverse. The objective of this research is to identify the importance of brand equity to University College Sabah Foundation and also come out with the suggestions and recommendations for University College Sabah Foundation in order to develop sustainable strategies. This research was done by distributing 291 questionnaires that were distributed manually and using electronic method in selected area which is within the internal organization of University College Sabah Foundation. Findings showed three areas of their greatest concerns which are brand awareness, brand association and perceived quality. Further, this paper highlighted the things that are necessary and needed improvement.